Isolation of Trichoderma strains from rhizospheric soil and assessment of their potential for biofertilizer from freshwater aquaculture pond sediment - QUACH VAN CAO THI; TRAN HOANG NHAN; NGUYEN VIET KHANH HUNG; NGUYEN PHUONG THUY (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Thi QVC, Nhan TH, Hung NVK, Thuy NP. 2024. Isolation of Trichoderma strains from rhizospheric soil and assessment of their potential for biofertilizer from freshwater aquaculture pond sediment. Biodiversitas 25: 2866-2876. Trichoderma spp. are filamentous fungi found in almost all soils and can synthesize massive quantities of cellulase enzymes which can simply break down cellulose polysaccharides. Freshwater water aquaculture pond sediment has caused some environmental pollution which is required to be properly dealt with. The objective of this study was to isolate Trichoderma strains from rhizosphere soil and to evaluate their potential for biofertilizer from freshwater aquaculture pond sediments. Twenty-six strains of Trichoderma spp. were isolated from soil. The Carboxymethyl Cellulose (CMC) degrading ability of the S25 strain was extremely strong, with a halo diameter zone measuring 8.9±3.8 cm. According to the BLAST result, there was 99.11% similarity between S25 strains and Trichoderma asperelloides, with a max score of 1011 and an E-value of 0.0. The T. asperelloides S25 was selected for bioproduct production. The use of T. asperelloides S25 bioproduct passively enhanced the efficient decomposition of organic fertilizers. After just 30 days of incubation, total organic matter content was ? 30% and material had a spongy, soft, and brown-black in color. According to the Government of Vietnam’s Decree No. 14/2019/ND-CP on fertilizer management, dated September 14, 2019, all treatments were chosen for the production of granular bio-compost. These findings highlight the potential of bioproduct T. asperelloides S25 for sustainable aquaculture practices and organic waste management.